Interaction of glucose sensing and leptin action in the brain - Rosa J.W. Li; Song-Yang Zhang; Tony K.T. Lam (Molecular Metabolism, 2020)
Background: In response to energy abundant or deprived conditions, nutrients and hormones activate hypothalamic pathways to maintain energy and glucose homeostasis. The underlying CNS mechanisms, however, remain elusive in rodents and humans. Scope of review: Here, we first discuss brain glucose sensing mechanisms in the presence of a rise or fall of plasma glucose levels, and highlight defects in hypothalamic glucose sensing disrupt in vivo glucose homeostasis in high-fat fed, obese, and/or diabetic conditions. Second, we discuss brain leptin signalling pathways that impact glucose homeostasis in glucose-deprived and excessed conditions, and propose that leptin enhances hypothalamic glucose sensing and restores glucose homeostasis in short-term high-fat fed and/or uncontrolled diabetic conditions. Major conclusions: In conclusion, we believe basic studies that investigate the interaction of glucose sensing and leptin action in the brain will address the translational impact of hypothalamic glucose sensing in diabetes and obesity.